Genetic link determining the maternal-fetal circulation of vitamin D - Sampathkumar, Aparna (2021)
Vitamin D is an essential micronutrient whose demand is heightened during pregnancy to support the growth of the fetus. Furthermore, the fetus does not produce vitamin D and hence relies exclusively on the supply of maternal vitamin D through the placenta. Vitamin D inadequacy is linked with pregnancy complications and adverse infant outcomes. Hence, early predictive markers of vitamin D inadequacy such as genetic vulnerability are important to both mother and offspring. In this multi-ethnic Asian birth cohort study, we report the first genome-wide association analysis (GWAS) of maternal and fetal vitamin D in circulation. For this, 25-hydroxyvitamin D (25OHD) was measured in the antenatal blood of mothers during mid gestation (n=942), and the cord blood of their offspring at birth (n=812). Around ~7 million single nucleotide polymorphisms (SNPs) were regressed against 25OHD concentrations to identify genetic risk variants. About 41% of mothers had inadequate 25OHD (≤75nmol/L) during pregnancy. Antenatal 25OHD was associated with ethnicity [Malay (Β=-22.32nmol/L, p=2.3×10-26); Indian (Β=-21.85, p=3.1×10-21); reference Chinese], age (Β=0.47/year, p=0.0058), and supplement intake (Β=16.47, p=2.4×10-13). Cord blood 25OHD highly correlated with antenatal vitamin D (r=0.75) and was associated with ethnicity [Malay (Β=-4.44, p=2.2×10-7); Indian (Β=-1.99, p=0.038); reference Chinese]. GWAS analysis identified rs4588, a missense variant in the group-specific component (GC) gene encoding vitamin D binding protein (VDBP), and its defining haplotype, as a risk factor for low antenatal (Β=-8.56/T-allele, p=1.0×10-9) and cord blood vitamin D (Β=-3.22/T-allele, p=1.0×10-8) in all three ethnicities. We also discovered a novel association in a SNP downstream of CYP2J2 (rs10789082), a gene involved in 25-hydroxylation of vitamin D, with vitamin D in pregnant women (Β=-7.68/G-allele, p=1.5×10-8), but not their offspring. As the prevention and early detection of suboptimal vitamin D levels are of profound importance to both mother and offspring's health, the genetic risk variants identified in this study allow risk assessment and precision in early intervention of vitamin D deficiency.